Development of dermopharmaceutical forms based on the fruit of Alchornea cordifolia (Euphorbiaceae) for the treatment of dermatophytes - Koffi Armand Angely; Tuo Awa; Aka Sandrine Armelle; Yeo Alain; N'Guessan Clemence; N'Guessan Alain; Kouassi Kouakou Eugène (Wolters Kluwer Medknow Publications, 2019)
Our work was to develop an ointment and a lotion from the fruit juice of Alchornea cordifolia for the treatment of dermatophytes. The juice from the cold pressing of the fruit pulp of A. cordifolia was lyophilized. The ointments and lotions obtained from the lyophilizate have been evaluated in vitro on different Trichophyton species (Trichophyton rubrum, Trichophyton interdigitale, Trichophyton soudanense, and Trichophyton mentagrophytes) according to two techniques, incorporation and direct connection.In vivo tests on white mice were performed after T. mentagrophytes infestation on scarified skin parts. The reference substance was griseofulvin. The 125 mg/ml lyophilizate solution of the fruit pulp showed an activity identical to that of the 125 mg/ml solution of griseofulvin. The lotions were made with ethanol at different degrees and at concentrations of 1/50 and 1/100. Ointments at different concentrations of the lyophilizate (20%, 33%, and 50%) were made with different types of excipients. All lotions and ointments showed in vitro antifungal activity identical to that of griseofulvin up to 16 and 30 days of incubation. The ointments showed better in vivo activity compared to lotions, and the 50% vaseline-based ointment revealed an activity identical to that of griseofulvin, with a healing time of 8 days. The lyophilizate of A. cordifolia fruit juice was formulated as an ointment and lotion, maintained a good antifungal activity in vitro and in vivo on Trichophyton species, compared to griseofulvin.